Late-Onset Bartter Syndrome Type II Due to a Novel Compound Heterozygous Mutation in KCNJ1 Gene: A Case Report and Literature Review - Tian, Mi; Peng, Hui; Bi, Xin; Wang, Yan-Qiu; Zhang, Yong-Zhe; Wu, Yan; Zhang, Bei-Ru (Frontiers in Medicine, 2022)
Background: Bartter syndrome (BS) type II is a rare autosomal recessive or dominant renal tubular disorder caused by mutations in the KCNJ1 gene, which encodes the apical renal outer medullary potassium (ROMK) channel in the thick ascending limb (TAL) of Henle’s loop. BS type II is usually believed to represent a disorder of infancy and is seldom seen in the adult period. Case presentation: A 34-year-old woman was admitted with generalized body numbness and hand convulsion without growth retardation. Laboratory tests showed hypokalemic metabolic alkalosis, hyperreninemic hyperaldosteronism, and nephrocalcinosis. She was initially misdiagnosed during the diagnosis process and finally was diagnosed with late-onset BS type II by genetic testing through next-generation sequencing combined with Sanger sequencing. A novel compound heterozygous p.Leu207Ile/p. Cys308Arg variants in exon 5 of the KCNJ1 gene from her parents were identified and speculated to be pathogenic gene variations. Conclusion: We report a case of late-onset BS type II with a novel compound heterozygous mutation of KCNJ1. Both variants were new and never reported. Our report could have a significant impact on the diagnosis of BS in other patients without typical clinical presentations and emphasize the importance of gene investigation. Keywords: Bartter syndrome type II, KCNJ1 gene mutation, nephrocalcinosis, hypokalemia, late onset